Hyponatremia: Case series with review of literature - Madhumita Murthy; S Chatterjee; R Nigam; D. Kosam (International Journal of Medical Research and Review, 2015)
Hyponatremia is the most common fluid & electrolyte disorder prevalent in hospital settings, manifesting in form of wide spectrum of clinical symptoms resulting in increased morbidity and duration of hospital stay in critically ill patients. Here we are presenting three cases of diselectrolytemia which were later diagnosed to be cases of hyponatremia. The pathophysiology, clinical signs and symptoms along with recent guidelines for treatment of a case of hyponatremia is also discussed here in details.